Quality Grade Has No Effect on Top Sirloin Steaks Cooked to Multiple Degrees of Doneness - B. A. Olson; E. A. Rice; J. M. Gonzalez; J. L. Vipham; M. D. Chao; T. A. Houser; E. A. Boyle; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2019)
Objective:The objective of this study was to evaluate the effect of cooking top sirloin steaks from four quality grades to multiple degrees of doneness (rare, medium, well-done) on beef palatability traits. Study Description:Beef top sirloin butts (n = 60; 15/quality grade) from four U.S. Department of Agriculture quality grades [Prime, Top Choice (Modest and Moderate marbling), Low Choice, and Select] were selected from a Midwest beef processor. Top butts were transported to the Kansas State University Meat Laboratory, fabricated into 1-in steaks, vacuum packaged, and aged for 28 days at 39.2°F. Following aging, steaks were frozen until cooked for consumer sensory analysis and Warner-Bratzler shear force. The Bottom Line:These results indicate that quality grade has no effect on the eating quality of top sirloin steaks. Therefore, it is unnecessary for consumers, retailers, and foodservices to pay premium prices for higher quality top sirloin steaks, regardless of the degree of doneness they will be cooked to.
Keywords: consumer; degree of doneness; sirloin